Influence of Hydrological Parameters on the Biodiversity of the BerettyóRiver I. - Pregun, Csaba; Tamás, János (Acta Agraria Debreceniensis, 2005)
The DIRECTIVE 2000/60/EC OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL orders the measurement of the state of natural and artifical waters. We therefore applied environmental qualification methods, which allow inductions of the searched area in environmental management, conservation and water quality protection points of view. These methods are accepted in interdisciplinary sciences, and are in use in Hungarian and international practice. We applied the range data measured along the Berettyó River, and ratified by the remote sensing, to count hydrological-hydraulical attributes of the stream, by the framework of the Hec-Ras programme. We processed the physical, chemical and biochemical water qualifications, determined the MMCP-index (the point-system of the Hungarian macrozoobenthos taxons), and estimated the Spencer index-numbers, which were based on complex environmental qualification and bioindication. Appointed, that the different results of researches are not inconsistent. This results together the spatial analysis reveal the natural and anthroponetic specialities of the river and the landscape, which determine the environmental flavours and biodiversity. The bioindicators represent better environmental status, than the physical, chemical and biochemical parameters. The natural conservationist importance of drainage canal network of Bihari-Plain is appreciated by these facts.